Cronologia vieții literare românești – Eminescu (ianuarie 2000) - Bianca Burța-Cernat (Revista de Istorie și Teorie Literară)
The present selection of documentary material is meant to highlight the articles on Mihai Eminescu in the journals issued in January 2000 that marked 150 years since the Romanian national poet’s birth. The year 2000 was declared “Eminescu’s Year” by the Romanian authorities and a number of works and events came to the forefront of the cultural stage. The Romanian Literary Chronology: The Post-Communist Period – elaborated by a group of researchers at the “G. Călinescu” Institute for Literary History and Theory of the Romanian Academy composed of Biana Burța-Cernat (publishing coordinator), Paul Cernat, Carmina Cojocaru, Marija Nenadić, George Neagoe and Andrei Milca – records the opinions generated by these events and the impact of this celebration.